Thorough the Application of Individual Guidance in an Effort to Improve Learning Outcomes Thematic Content of Natural Siciences on Energy in Class II Student of Elementary School 02 Gondangmanis - Prasetyo, Suyamto Eko (Universitas Sebelas Maret, 2022)
The purpose of this study was to improve learning achievement Thematic Content of Natural Sciences energy material through individual guidance to class III students of 02 Gondangmanis State Elementary School, Karanganyar. The subjects of this study were class III students of Public Elementary Schools 02 Gondangmanis with a total of 17 students. The source of data in this study were the results of tests and documents. The data validity test technique uses data source triangulation techniques and method triangulation. The data analysis technique used in this study is interactive analysis. The average value of before the first cycle was 52.94, cycle I was 75 88 , cycle II, 87.64 and cycle III 96.47. Meanwhile, with KKM of 70 points, learning mastery increased since before cycle 51.00% cycle I, 76.64, Cycle II, 87.64% and Cycle III reached 100%. Thus in this study each cycle always experiences a significant increase in achievement.